Microencapsulation of Lysiphyllum strychnifolium extract using pectin as a carrier matrix and its characterization - Goli, Arman Syah; Leanpolchareanchai, Jiraporn; Chewchinda, Savita; Yahuafai, Jantana; Nontakham, Jannarin; Sato, Hitoshi; Sato, Vilasinee Hirunpanich (Life Sciences, Medicine and Biomedicine, 2022)
Lysiphyllum strychnifolium (Craib) A. Schmitz (LS, Fabaceae) is one of the folklore medicines in Thailand. The previous studies have demonstrated several pharmacological activities and high polyphenolic substances possessed by this plant. However, the suitable encapsulation of LS extract has not been discovered. This study aimed to develop LS microcapsules using spray-drying technique with pectin as a carrier. Moreover, the powder analysis and characterization were also conducted. The effects of inlet temperatures (80, 100, and 120°C) and carrier concentrations (1, 5, and 10 %w/v) on the encapsulation yield (EY), encapsulation efficiency (EE), total phenolic content (TPC), and main markers (trilobatin and yanangdaengin) of LS microcapsules were studied. Finally, the characterization was investigated by Fourier transform infrared (FTIR), X-ray diffraction (XRD), differential scanning calorimetry (DSC), and scanning electron microscopy (SEM). The obtained results indicated that S2 microcapsule formulation, pectin to extract ratio 10:1 (w/w) at inlet temperature of 100°C, was chosen as the optimal condition because of the positive tendency to acquire higher EE as pectin level was increased. On the contrary, the level of TPC and markers was reduced due to the more addition of pectin. The FTIR, XRD, and DSC results suggested that the well-encapsulated microcapsules were obtained for S2 formulation and SEM represented the semi-spherical structure of its microstructures. The development of LS microcapsules with the proximity to gain the advantageous powder analysis and characteristic has been achieved. Therefore, this approach could be used for the subsequent manufacturing of LS extract.